Ambient PM2.5 and its chemical constituents on lifetime-ever pneumonia in Chinese children: A multi-center study. (January 2021) - Shi, Wenming; Liu, Cong; Annesi-Maesano, Isabella; Norback, Dan; Deng, Qihong; Huang, Chen; Qian, Hua; Zhang, Xin; Sun, Yuexia; Wang, Tingting; van Donkelaar, Aaron; Martin, Randall V.; et al.
Graphical abstract: Highlights: Long-term exposure to ambient PM2.5 increased the risks of childhood pneumonia. NO3 −, NH4 + and OM dominated the health effects of PM2.5 on pneumonia in children. Children in urban areas and breastfeeding < 6 months had higher risks of pneumonia. Children aged < 5 yrs enhanced the risk of pneumonia when exposure to ambient PM2.5 . Abstract: The long-term effects of ambient PM2.5 and chemical constituents on childhood pneumonia were still unknown. A cross-sectional study was conducted in 30, 315 children in the China Children, Homes, Health (CCHH) project, involving 205 preschools in six cities in China, to investigate the long-term effects of PM2.5 constituents on lifetime-ever diagnosed pneumonia. Information on the lifetime-ever pneumonia and demographics were collected by validated questionnaires. The lifetime annual average ambient PM2.5, ozone and five main PM2.5 constituents, including SO4 2−, NO3 −, NH4 +, organic matter (OM) and black carbon (BC), were estimated according to preschool addresses by a combination of satellite remote sensing, chemical transport modeling and ground-based monitors. The prevalence of lifetime-ever diagnosed pneumonia was 34.5% across six cities and differed significantly among cities (p = 0.004). The two-level logistic regression models showed that the adjusted odds ratio for PM2.5 (per 10 µg/m 3 ) and its constituents (per 1 µg/m 3 )-SO4 2−, NO3 −, NH4 +, and OM were 1.12 (95% CI:1.07–1.18), 1.02 (1.00–1.04), 1.06 (1.04–1.09), 1.05 (1.03–1.07) and 1.09 (1.06–1.12), respectively. Children in urban area, aged < 5 years and breastfeeding time < 6 months enhanced the risks of pneumonia. Our study provided robust results that long-term levels of ambient PM2.5 and its constituents increased the risk of childhood pneumonia, especially NH4 +, NO3 − and OM.